2022
DOI: 10.1021/acs.analchem.2c01308
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Renal-Clearable Multicolor Fluorescent Silicon Nanodots for Tumor Imaging and In Vivo H2O2 Profiling

Abstract: Fluorescent silicon nanodots have shown great prospects for bioimaging and biosensing applications. Although various fluorescent silicon-containing nanodots (SiNDs) have been developed, there are few reports about renal-clearable multicolor SiNDs. Herein, renal-clearable multicolor fluorescent SiNDs are synthesized by using silane molecules and organic dyes through a facile one-step hydrothermal method. The fluorescence of the resulting SiNDs can be tuned to blue (bSiNDs), green (gSiNDs), and red (rSiNDs) by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…A number of studies on the cytotoxicity of Si QDs have demonstrated their low toxicity. , Toxicity assessments taken in Caenorhabditis elegans models verified that Si QDs could not affect their longevity or reproductivity in the short term, suggesting that Si QDs have negligible in vivo toxicity to Caenorhabditis elegans . In 2022, Jiang et al validated that Si QDs with a small average size (less than 3.4 nm) are a renal-clearable nanomaterial possessing low potential systemic toxicity . The renal clearance of the obtained Si QDs exceeded 75% ID within 12 h, providing high biosafety of Si QDs for biomedical applications.…”
Section: Properties Of Si Qdsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies on the cytotoxicity of Si QDs have demonstrated their low toxicity. , Toxicity assessments taken in Caenorhabditis elegans models verified that Si QDs could not affect their longevity or reproductivity in the short term, suggesting that Si QDs have negligible in vivo toxicity to Caenorhabditis elegans . In 2022, Jiang et al validated that Si QDs with a small average size (less than 3.4 nm) are a renal-clearable nanomaterial possessing low potential systemic toxicity . The renal clearance of the obtained Si QDs exceeded 75% ID within 12 h, providing high biosafety of Si QDs for biomedical applications.…”
Section: Properties Of Si Qdsmentioning
confidence: 99%
“…22 In 2022, Jiang et al validated that Si QDs with a small average size (less than 3.4 nm) are a renal-clearable nanomaterial possessing low potential systemic toxicity. 44 The renal clearance of the obtained Si QDs exceeded 75% ID within 12 h, providing high biosafety of Si QDs for biomedical applications. However, different surface features can induce discrepancies in cytotoxicity and biodistribution to Si QDs.…”
mentioning
confidence: 94%
“…17,25 Recently, several ultrasmall luminescent nanomaterials have been tailored for in vivo PL imaging, such as quantum dots (QDs), metal nanoclusters (NCs), lanthanide-doped NPs, and silicon NPs. [26][27][28][29][30][31][32] The developed ultrasmall nanoprobes have been implemented to analyze in vivo diseases -especially cancer-associated hallmarks, such as ions, small molecules, nucleic acids, proteins and enzymes. As such, it is anticipated that the ultrasmall luminescent nanoprobes will serve as potent PL imaging tools and provide a solution to in vivo imaging.…”
Section: Introductionmentioning
confidence: 99%
“…This approach, if applicable, could initiate the therapeutic process only within tumor sites instead of other normal ones, hopefully leading to the concurrent of high curative outcome and ignorable side effect. In recent years, biomolecule-derived CNDs, such as folate, bacteria, and hemoglobin, have exhibited specific targeting ability or affinity for some cells or organs. In particular, cancer cell membrane-camouflaged nanoparticles are endowed with immune escaping and homologous targeting ability. Taking the rich element composition and excellent homologous targeting ability into consideration, cancer cells may be a favorable carbon source for the preparation of N/S/P-codoped CNDs with both PTT/PDT synergistic therapy and targeting capabilities as well as imaging ability.…”
Section: Introductionmentioning
confidence: 99%